Lakota Texts : Narratives of Lakota Life and Culture in the Twentieth Century - Pustet, Regina, 1963-2013 (Book collections on Project MUSE., 2021)
Lakota Texts is a treasure trove of stories told in the original language by modern Lakota women who make their home in Denver. Sometimes witty, often moving, and invariably engaging and fascinating, these stories are both autobiographical and cultural.